Case Report: Maintaining a balance between vascular access patency and stable dissection status in a hemodialysis patient with unrepaired type A aortic dissection - Lai, Qiquan; Chen, Ling; Gao, Xuejing; Tie, Hongtao; Wan, Ziming (Frontiers in Cardiovascular Medicine, 2025)
IntroductionType A aortic dissection (AD) is a lethal situation with high mortality within short time after onset. We present here a rare hemodialysis patient whose condition was comorbid with unrepaired type A AD. The challenge we face is whether low-molecular-weight heparin (LMWH) should be used during dialysis.Case presentationA 72-year-old man with a history of hemodialysis for 2 years and 7 months sought medical attention due to thrombosis of the dialysis catheter. He had been diagnosed with an unrepaired type A aortic dissection (involving the aortic root, the ascending aorta, the aortic arch, the descending aorta, the abdominal aorta, the left common iliac artery, and the femoral artery) for more than 5 years. LMWH was not given during the previous dialysis process because of concerns about the rupture of the dissection. The lesion was salvaged via urokinase thrombolysis. However, the anticoagulant-free dialysis pattern occasionally caused dialyzer clotting and further increased the risk of catheter dysfunction. The patient repeatedly experienced dysfunction of the catheter in the following 8 months, with 2 episodes resolved via thrombolysis and 2 episodes replaced with new catheters. Finally, LMWH was used for each dialysis session to prevent thrombosis, with the dosage gradually increasing from 1,000 units to 2,000 units. The dosage of 2,000 units could support sufficient 4-hour dialysis for each session. Twenty-five months have passed since then, the patient has not experienced any further occlusion of the catheter, and the aortic dissection has not shown obvious changes (neither obvious expansion nor rupture).ConclusionReducing the dosage of LMWH during hemodialysis is a feasible solution to maintain a balance between hemodialysis access patency and stable dissection status in this particular patient.